The Impact of Intermittent Fasting on Alzheimer's Disease Risk: A Literature Review - Stencel, Nicola Joanna; Szczot, Jakub; Krala-Szkaradowska, Magdalena; Skrzypczak, Katarzyna Oktawia; Stuczyński , Sebastian Krzysztof (Quality in Sport, 2024)
Introduction and purpose: In the face of an aging population, the increasing number of elderly individuals raises the incidence of age-related conditions, including Alzheimer's disease (AD), which is a leading cause of global disability and a significant burden on society. The lack of effective treatments for AD underscores the importance of prevention. Recent reports suggest that intermittent fasting (IF) may counteract the disease processes associated with AD and serve as a potential preventive strategy. This review aims to outline the impact of IF on the risk of developing Alzheimer's disease. Materials and methods: A literature search was conducted using the medical databases PubMed and Google Scholar. Articles were retrieved in English, employing the keywords: “Alzheimer’s disease”, “dementia”, “intermittent fasting”, “ketone bodies”, “cognition”. State of knowledge: IF is a dietary regimen involving cyclic restriction of food intake, practiced in many cultures and religions. The interest in IF has increased due to its numerous health benefits, and recent studies indicate its potential in delaying and preventing pathological processes associated with AD, such as β-amyloid accumulation, neuroinflammation, and vascular damage, making IF a potentially protective intervention against neurodegeneration. Summary: IF is a promising strategy for improving cognitive function and brain health. Due to the limited number of studies conducted on humans, further research is needed to confirm its effectiveness in preventing AD.